Gross tumour volume delineation in anal cancer on T2-weighted and diffusion-weighted MRI – Reproducibility between radiologists and radiation oncologists and impact of reader experience level and DWI image quality. (September 2020) - Min, Lisa A.; Vacher, Younan J.L.; Dewit, Luc; Donker, Mila; Sofia, Carmelo; van Triest, Baukelien; Bos, Paula; van Griethuysen, Joost J.W.; Maas, Monique; Beets-Tan, Regina G.H.; Lambregts, Doenja M.J.
Highlights: MRI is increasingly used for gross tumour volume (GTV) delineation in anal cancer. GTV delineation is reproducible between radiologists and radiation oncologists. Diffusion-weighted MRI (DWI) renders similar results as anatomical (T2-weighted) MRI. Artefacts are common on DWI and may limit its use for radiotherapy planning. Abstract: Purpose: To assess how gross tumour volume (GTV) delineation in anal cancer is affected by interobserver variations between radiologists and radiation oncologists, expertise level, and use of T2-weighted MRI (T2W-MRI) vs. diffusion-weighted imaging (DWI), and to explore effects of DWI quality. Methods and materials: We retrospectively analyzed the MRIs (T2W-MRI and b800-DWI) of 25 anal cancer patients. Four readers (Senior and Junior Radiologist; Senior and Junior Radiation Oncologist) independently delineated GTVs, first on T2W-MRI only and then on DWI (with reference to T2W-MRI). Maximum Tumour Diameter (MTD) was calculated from each GTV. Mean GTVs/MTDs were compared between readers and between T2W-MRI vs. DWI. Interobserver agreement was calculated as Intraclass Correlation Coefficient (ICC), Dice Similarity Coefficient (DSC) and Hausdorff Distance (HD). DWI image quality was assessed using a 5-point artefact scale. Results: Interobserver agreement between radiologists vs. radiation oncologists and between junior vs. senior readers was good–excellent, with similar agreement for T2W-MRI and DWI (e.g. ICCs 0.72–0.94 for T2W-MRI and 0.68–0.89 for DWI). There was a trend towards smaller GTVs on DWI, but only for the radiologists ( P = 0.03–0.07). Moderate-severe DWI-artefacts were observed in 11/25 (44%) cases. Agreement tended to be lower in these cases. Conclusion: Overall interobserver agreement for anal cancer GTV delineation on MRI is good for both radiologists and radiation oncologists, regardless of experience level. Use of DWI did not improve agreement. DWI artefacts affecting GTV delineation occurred in almost half of the patients, which may severely limit the use of DWI for radiotherapy planning if no steps are undertaken to avoid them.